Níveis de cloreto presentes no sorgo biomassa em função de fontes de adubação potássica e épocas de colheita - Silvério, Patrícia Chiara (2016)
The Brazilian energetic matrix is one of the world's largest domestic supply of electricity from renewable sources. Sugarcane bagasse, the second largest renewable source, highlights the importance of sugarcane plants in this market segment. In order to make a better use of the sugarcane plants boilers, inoperative in the off-season after maintenance, the use of another crops such as sorghum biomass (Sorghum bicolor L. Moench), which has a low production cost, short cycle and high yield for the generation of electric energy through the direct burning of the biomass is pointed out. However, this alternative has shown an inconvenience: the presence of chloride in the biomass, which at high temperature promotes the corrosion of the boilers. In order to explore the existing gaps regarding crop management and the consequent assimilation of the chloride by the plant, was evaluated the influence of different fertilizations and harvest times of the sorghum biomass and chloride levels in biomass. This experiment was carried out in the municipality of Águas de Santa Bárbara, State of São Paulo, in the 2015/2016 crop with Palo Alto® hybrid in the 0.5m between plants and 7.5m plants per linear meter between rows. The experiment was developed in randomized blocks with 4 replications, 3 treatments for potassic sources in the fertilization and 4 treatments at the harvest times. The results obtained showed that the fertilization sources do not affect the productivity, however, when KCl is used, higher chloride levels are observed in biomass sorghum. The period with the lowest level of chloride in the biomass is milky grain, characterizing the best harvesting period for sorghum biomass